O trabalho do professor de Sala de Recursos e o ensino não presencial no Brasil (2020) - Lima, Alyne Cristine Domene Martins de (Universidade Federal de São Carlos, 2022)
This study proposes to identify and analyze how the work of the teacher in the resource room happened, observing the limits and possibilities in the context of the physical distancing in the year of 2020, when, due to the COVID-19, infectious disease that spread through different continents in a very short amount of time, and following the general orientations of the Opinion 05/2020, it was assured to the target students of the Special Education the non-presential teaching. This way, the study was guided by the question: how was the resource room teacher's work organized and applied during the non-presential teaching in the year 2020? Seeking to answer the research problem, it was developed with the general objective: identify and analyze the organization and the teacher's work functioning in the resource room in the basic education of the Brazilian public system in the year of 2020. Also, as specific objectives: a) identify and analyze official national documents and external directions that guided the non-presential teaching in this year; b) characterize the proposals for the work of the resource room in the non-presential teaching; c) point and analyze the proposal of non-presential teaching, in the year 2020, in the teachers' pedagogical practice in the resource room. The present research, of qualitative character, is characterized as a descriptive study. The data collection happened from an online questionnaire with open and closed questions. From the participation of 55 resource room teachers who acted in the non-presential teaching in 2020, it was possible to identify three axes of analysis. 1) planning and digital resources – formation for the non-presential teaching; 2) the contact with the students: the family participation; 3) the resource room teacher's work articulation along with the common teaching teachers and school management. The results of this study showed that the shortage of resources, the lack of internet access and formation to use these resources, on the teachers’ side and also on the students’ families’ side, could be characterized as disadvantage factors for the resource room teacher's work development. The results also highlighted that the articulation with the families (support) and the common teaching teachers highly contributed to the resource room teacher's work durin the emergency teaching model.
The work of the teacher in the resource room and the non-presential teaching in Brazil (2020)
Keywords: Educação Especial; Sala de Recursos; Ensino não presencial; COVID-19; Educação Básica; Special Education; Resource Room; Non-presential teaching; COVID-19; Basic Education; CIENCIAS HUMANAS::EDUCACAO